PENGARUH KEPEMILIKAN INSTITUSIONAL, KOMISARIS INDEPENDEN, KOMITE AUDIT, LEVERAGE, UKURAN PERUSAHAAN DAN RETURN ON ASSETS TERHADAP TAX AVOIDANCE - Nurul Azizah Al Laurent, 13.05.52.0018; Nuswandari, Cahyani (Students' Journal of Accounting and Banking, 2017)
The purpose of this research is to analyze the effect of institutional ownership, independent commissioner , audit committee, leverage, company size, and return on assets to the tax avoidance on manufacturing companies listed in Indonesia Stock Exchange 2013-2015 period. Data used in this research is secondary data, the data in this study were obtained from the Financial Statements and ICMD (Indonesian Capital Market Directory) 2013-2015. The sampling method used is purposive sampling. The amount of data that is processed as many as 161 companies. Methods of data analysis using multiple linear regression. The results of research showed that leverage and return on asset has effect on tax avoidance, while variable institutional ownership, independent commissioner, audit committee and company size has no effect on tax avoidance.Keywords: Tax Avoidance, Institutional Ownership, Independent Commissioner, Audit Committee, Leverage, Company Size, and Return On Assets